2019
DOI: 10.1109/access.2019.2919957
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Autonomic Provisioning and Management of QoS in SDN Networks

Abstract: In today's Internet, killer network services and applications, such as video and audio streaming, network storage, and online video games, are pushing the network infrastructure resources to the edge. By design and for the most part, the Internet is the best offer delivery ecosystem with little or no endto-end quality-of-service (QoS) guarantees. Even, frameworks, such as IntServ and DiffServ that were designed and implemented to provide QoS guarantees, still fail to solve this problem at a wide scale. Softwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 230 publications
(346 reference statements)
0
20
0
Order By: Relevance
“…These determined values are used by the monitoring module to manage loads when a new connection is made. When connection usage reaches 80%, a different path is selected instead of the shortest one, to prevent packet loss [16,17]. A survey on managing QoS in SDN Networks [17] involved reviewing various methods to monitor and manage QoS.…”
Section: B Analysis Of Approaches To Network Performance Inmentioning
confidence: 99%
See 1 more Smart Citation
“…These determined values are used by the monitoring module to manage loads when a new connection is made. When connection usage reaches 80%, a different path is selected instead of the shortest one, to prevent packet loss [16,17]. A survey on managing QoS in SDN Networks [17] involved reviewing various methods to monitor and manage QoS.…”
Section: B Analysis Of Approaches To Network Performance Inmentioning
confidence: 99%
“…When connection usage reaches 80%, a different path is selected instead of the shortest one, to prevent packet loss [16,17]. A survey on managing QoS in SDN Networks [17] involved reviewing various methods to monitor and manage QoS. The authors concluded that there is a lack of extensive analysis on the network performance parameters, including delay, throughput and jitter, particularly when dealing with variety of network applications, such as video, audio, and data, in one testbed framework.…”
Section: B Analysis Of Approaches To Network Performance Inmentioning
confidence: 99%
“…Similar to work in [64,65], the revenue of serving a VN request is defined by summing up the required CPU and bandwidth resource for VN requests as shown in Equation (7), where α and β are the weights. Although revenue is the metric that InP will gain by accepting VN requests, it is not very considerable without knowing the cost of InP.…”
Section: Profitmentioning
confidence: 99%
“…Network virtualization and orchestration are key processes for network slicing, where software-defined network (SDN) and network function virtualization (NFV) are the key enabling technologies for network orchestration [4,5]. In addition, SDN can manage and deploy the service requirements automatically by decoupling the transmitting layer and control layer [6,7]. It is specified to leverage the benefits of network virtualization to allow high flexibility among various mobile and IoT services in multi-domain heterogeneous converged optical networks.…”
Section: Introductionmentioning
confidence: 99%
“…For each state st at time t there is a set A(st) of possible actions. The AI gets either bonuses or punishments for the acts it performs to get the system to do what the programmer wants [89]. The aim is to maximize overall reward.…”
Section: Reinforced Learningmentioning
confidence: 99%